MODEL PEMBELAJARAN MENULIS TEKS ANEKDOT MELALUI VIRTUAL LEARNING PADA KURIKULUM MERDEKA BELAJAR UNTUK SISWA SMA - Puspitoningrum, Encil; Agan, Subardi; Rahmayantis, Marista Dwi (LPPM Universitas PGRI Silampari Lubuklinggau, 2023)
The purpose of this article is to describe efforts to implement virtual learning at the high school level. This article is a conceptual idea that was carried out using the literature study method. Its activities include gathering information relevant to the topic of the research problem. Information is obtained from books, scientific papers, and other sources. The results of the development of the learning model in this article describe: (1) analysis of the learning needs of writing anecdote texts through virtual learning in the independent learning curriculum, (2) developing a learning model for writing anecdotal texts through virtual learning in the independent learning curriculum, (3) application of the model learning to write anecdotal texts through virtual learning in the independent learning curriculum, and (4) the effectiveness of learning to write anecdotal texts through virtual learning in the independent learning curriculum. The conclusion of this article is that the results of a description of the conceptual idea of ​​learning to write anecdotal texts through virtual learning in the independent learning curriculum can be an effective alternative learning model by considering several other integrated factors. Other integrated factors such as the active involvement of teachers and students when using the media used. The device used must also be supported by a smartphone, online application, good network.